Massive Spontaneous Hemothorax as a Complication of Apixaban Treatment - M. Abu Hishmeh; P. Srivastava; Q. Lougheide; M. Srinivasan; S. Murthy (Case Reports in Pulmonology)
Introduction. Hemothorax is usually related to chest or iatrogenic trauma from procedures such as central lines and thoracentesis. Spontaneous hemothorax is defined as pleural fluid hematocrit greater than 50% of serum hematocrit in absence of natural or iatrogenic trauma affecting the lung or pleural space. Coagulopathy secondary to anticoagulant use has been associated with spontaneous hemothorax. We present a case of spontaneous hemothorax in a patient taking apixaban for venous thromboembolism disease. To our knowledge, this is the first case report of apixaban as a cause of spontaneous hemothorax. Case Presentation. A 56-year-old woman with end-stage renal disease (ESRD) was diagnosed with upper extremity deep vein thrombosis (DVT) one month prior to presentation and was started on apixaban presented with dyspnea and left-sided pleuritic chest pain for two weeks. She was found to have left-sided large pleural effusion which was diagnosed as hemothorax. Other etiologies for spontaneous hemothorax were excluded and drainage by 12-French pigtail catheter achieved total resolution of hemothorax in three days. Discussion. Apixaban is a DOAC used to prevent stroke or thromboembolic events in patients with nonvalvular atrial fibrillation and to prevent recurrent venous thromboembolic disease. Events such as gastrointestinal, intracranial, and soft tissue bleeding have been well-documented. However, bleeding manifestation as hemothorax is seldom reported. Our patient presented with isolated left-sided large pleural effusion which was diagnosed as spontaneous hemothorax. 12-Fr pigtail catheter drainage was effective in the management of our patient and provided total resolution in three days. Conclusion. Spontaneous hemothorax is a rare complication of anticoagulant therapy and might not exhibit the usual radiological signs of traumatic hemothorax. Health care providers should have high index of suspicion for spontaneous hemothorax when evaluating new pleural effusion in patients receiving DOACs therapy. Drainage by small bore pigtail catheter might be as effective as larger chest tubes.